Serum Proteomic Changes in Pet Rabbits with Subclinical and Clinical Encephalitozoonosis in Thailand - Taksaon Duangurai; Onrapak Reamtong; Tipparat Thiangtrongjit; Siriluk Jala; Peerut Chienwichai; Naris Thengchaisri (Animals, 2025)
Encephalitozoon cuniculi causes both clinical and subclinical infections in rabbits, complicating a diagnosis due to the limitations of conventional tools like ELISA. This study analyzes serum proteomic profiles across clinical, subclinical, and healthy rabbits to identify discriminatory biomarkers. Serum from 90 pet rabbits (30 per group) was pooled (10 samples per pool, 3 pools per group) and analyzed using one-dimensional gel electrophoresis and mass spectrometry. The proteomic analysis revealed 109, 98, and 74 proteins expressed in healthy, subclinical, and clinical groups, respectively. Of these, 50, 40, and 33 proteins were unique to the healthy, subclinical, and clinical groups, respectively, with only 10 proteins shared across all. A total of 88 proteins were differentially expressed in infected groups compared to healthy controls. Importantly, 12 proteins were consistently upregulated in both subclinical and clinical infections. These include markers related to the immune response (beta-2-microglobulin, alpha-2-HS-glycoprotein), coagulation (antithrombin-III, alpha-1-antiproteinase S-1), vitamin A transport (retinol-binding proteins), lipid metabolism (apolipoprotein C-III), cytoskeletal regulation (actin-depolymerizing factor), extracellular matrix integrity (fibrillin 2), and oxidative stress (monooxygenase DBH-like 1). Additionally, Gc-globulin and ER lipid-raft-associated 1 were linked to immune modulation and signaling. These findings identify specific serum proteins as promising biomarkers for distinguishing subclinical from clinical encephalitozoonosis in rabbits, enabling an early diagnosis and effective disease monitoring.